Mechanical Behavior of Fiber Strapping Band for Infrastructure Rigid Pavement - Adnan, Adnan; Habibie , Habibie; Rahmawati , Rahmawati (Journal of Renewable Engineering, 2024)
The development of science, especially in the field of transportation, especially roads, requires adequate infrastructure in the form of rigid roads or pavements that are in accordance with conditions in the field. This study aims to analyze the addition of fiber strapping band by 0.75%, 1.25%, 1.75% to increase concrete compressive strength, and concrete tensile strength. Research Methods The experiment was conducted in the Civil Engineering laboratory of the University of Muhammadiyah Parepare. The results of the study were 0% (normal), 0.75%, 1.25% and 1.75% on fine aggregates. Testing of 28-day-old concrete on normal concrete amounted to 22.74 Mpa, on 0.75% fiber strapping band concrete amounted to 21.137 Mpa, on 1.25% strapping band fiber concrete amounted to 16.70 Mpa, and on 1.75% strapping band fiber concrete amounted to 17.26 MPa. The results of tensile testing of concrete at the age of 28 days, in normal concrete amounted to 5.889 MPa. For concrete with 0.75% fiber strapping band of 6.111 MPa. For concrete with 1.25% fiber strapping band of 5.556 MPa. For concrete with 1.75% fiber strapping band of 5.778 MPa. The results showed that the use of strapping bands as a substitute for fine aggregate in concrete had a considerable influence so that it experienced an increase in pressure on concrete by a certain percentage. Thus concrete with 0.75% fiber strapping band produces compressive strength plans and is suitable for use for rigid pavement pavement.